2013
DOI: 10.1021/jo401482b
|View full text |Cite
|
Sign up to set email alerts
|

Selectivities of Multicomponent [4 + 2]/[3 + 2] Cycloadditions of 3-Nitroindole with Substituted Alkenes: A DFT Analysis

Abstract: The chemo-, regio-, and stereoselectivities of multicomponent [4 + 2]/[3 + 2] domino cycloaddition reactions involving nitroindole derivatives with vinylethers and acrylates are studied computationnally and compared to experimental results. In this process, the nitroarene first reacts as an electron-deficient heterodiene with the electron-rich alkene following an inverse electron-demand [4 + 2] process, leading to a nitronate intermediate in a fully selective way. This intermediate exclusively interacts, in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…In our case, it is the stabilization of the resulting carbanion by the electron-withdrawing group which rationalizes the reaction between the two nucleophilic partners. [25] Having opened an access to hitherto unknown and novel compounds, we then investigated if further functionalizations were possible to obtain new polycyclic frameworks which might possess interesting biological activities. [26] To this purpose, 2-vinylindole (2 k) was reacted with N-tosyl-Nallylynamide (1 b) to give 4 kb, which could then be cyclized using Grubbs second-generation catalyst to afford 1,4diazocinoindole (10; Scheme 7).…”
mentioning
confidence: 99%
“…In our case, it is the stabilization of the resulting carbanion by the electron-withdrawing group which rationalizes the reaction between the two nucleophilic partners. [25] Having opened an access to hitherto unknown and novel compounds, we then investigated if further functionalizations were possible to obtain new polycyclic frameworks which might possess interesting biological activities. [26] To this purpose, 2-vinylindole (2 k) was reacted with N-tosyl-Nallylynamide (1 b) to give 4 kb, which could then be cyclized using Grubbs second-generation catalyst to afford 1,4diazocinoindole (10; Scheme 7).…”
mentioning
confidence: 99%
“…The latest technological era, along with a better understanding of mechanistic pathways allows for the speedy and clear identification of important products. In 2013, Isabelle and colleagues published one of the most notable selectivity in the Diels‐Alder domino/cascade approach [116] . They described a multicomponent process that included [4+2] and [3+2] cycloadditions.…”
Section: Selectivity In Diels‐alder Cycloaddition Pathwaymentioning
confidence: 99%
“…DFT calculations, reported on these multicomponent domino (4+2)/(3+2) cycloadditions of 3nitroindoles confirmed that, the endo approach with the regiochemistry observed experimentally was indeed the most favourable pathway for the primary (4+2) cycloaddition reaction. 59 The 3-nitroindole reacted through its LUMO as an electron-poor heterodiene in a concerted though asynchronous inverse demand hetero-Diels-Alder. The electronic rearrangements observed during this step were in line with the expected pathway and, for this first cycloaddition process, the FMO model provided perfectly reliable predictions (Scheme 40).…”
Section: (4+2)/(3+2) Cycloaddition Reactionsmentioning
confidence: 99%